Ứng dụng luật điều khiển mờ trong quá trình quyết định đường đi trên mạng - Châu, Nguyễn Hải (Journal of Computer Science and Cybernetics, 2016)
This paper presents a fuzzy approach to routing decision in networks. This approach allows us to find out more several paths ther low cost (in fuzzy meaning) to given destination. A fuzzy rule will be presented in order to extend or restrict set of directions from a source node to a given destination by considering queusing status of the node.